DESAIN SISTEM INFORMASI PENJUALAN ANEKA JASA BERBASIS E-COMMERCE (Studi Kasus: Ds.Teguhan Kec. Jiwan Kab. Madiun) - suluh langgeng swasono (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2022)
Â Abstractâ€” The use of technology during the COVID-19 pandemic is very useful, none other than in service transaction activities.With this technology, it can help service actors and buyers in conducting service transactions. Services in Teguhan Village were previously still classified as manual, In the transaction process which is still classified as manual, the buyer must go to the service center and queue. Based on the results of interviews and observations with service actors and buyers, There are several problems experienced during the Covid-19 pandemic, and the problems experienced include the difficulty of service actors in getting consumers due to the covid-19 pandemic buyers are reluctant to go to the service place because they have to queue In the constraints experienced by the Bersinar UMKM, it can be concluded that in an effort to support the community service business of Teguhan Village,it is necessary media information system in the form of system design. Therefore, the author will design an information system design for offering various services based on E-commerce where service actors can offer a variety of services that offered to consumers and so that consumers can make transactions online to avoid queues.